Casamino acids slow motility and stimulate surface growth in an extreme oligotroph. Issue 1 (5th December 2019) - Samuels, Toby; Pybus, David; Cockell, Charles S.
Summary: Environmental cues that regulate motility are poorly understood, but specific carbon and nitrogen sources, such as casamino acids (CAA), are known to stimulate motility in model organisms. However, natural environments are commonly more nutrient‐limited than laboratory growth media, and the effect of energy‐rich CAA on the motility of oligotrophic microorganisms is unknown. In this study, an extreme oligocarbotroph, Variovorax paradoxus YC1, was isolated from weathered shale rock within a disused mine level in North Yorkshire, UK. The addition of 0.1% CAA to minimal media significantly reduced the motility of YC1 after 72 h and inhibited swimming motility resulting in enhanced surface growth. We propose this response to CAA is a physiological adaptation to oligotrophy, facilitating the colonization of nutrient‐rich environments.